2015
DOI: 10.4238/2015.september.21.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single nucleotide polymorphisms in the ATP-binding cassette B1 gene on the clini­cal outcome of traumatic brain injury

Abstract: ABSTRACT. The critical role of ATP-binding cassette B1 (ABCB1) in the function of the blood-brain barrier led us to conducted this prospective study in order to investigate the clinical outcome of patients suffering from severe traumatic brain injury. A total of 182 patients with traumatic brain injury were included in our study. Genotyping of ABCB1 C3435T and G2677T/A was conducted using polymerase chain reaction-restriction fragment length polymorphism. Using multivariatelogistic regression analysis, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][80][81][82][83] Study design varied. Fifty-four publications described prospective cohort studies 16,17,[19][20][21][22][23][24][26][27][28][29][30][31]34,35,37,38,[40][41][42][43][44][46][47][48][49][50][51][52][53]…”
Section: Patient and Study Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][80][81][82][83] Study design varied. Fifty-four publications described prospective cohort studies 16,17,[19][20][21][22][23][24][26][27][28][29][30][31]34,35,37,38,[40][41][42][43][44][46][47][48][49][50][51][52][53]…”
Section: Patient and Study Demographicsmentioning
confidence: 99%
“…Ten studies explored the outcome impact of miscellaneous SNPs (which did not fit into the previously mentioned categories) across the spectrum of TBI severity. 58-61,63-65,68,70,80,81 The SNPs studied were related to genes coding for p53, 68 angiotensin-converting enzyme (ACE), 58 neuroglobulin, 63 adenosine triphosphate (ATP) binding cassette, 59,61 aquaporin (AQP)-4, 64 aromatase rs2470144/rs4646/ rs2470152, 65 poly adenosine diphosphate-ribose polymerase-1 (PARP-1) rs3219119/rs3219090, 70 mannose binding lectin-2 (MBL2)/ficolin-2 (FCN2; rs1800451, rs1800450, rs5050737, rs7096206; rs3124953, rs17514136, rs17549193, and rs7851696), 80 and calcineurin (PPP3CC; rs2443504, rs2461491, rs2469749, and rs10108011). 81 Several SNPs were found to be associated with variations in a range of outcomes: p53 arginine homozygotes were found to have a worse GOS at intensive care unit (ICU) discharge; 68 three ACErelated SNPs (C minor allele carriers for rs4461142, C minor allele carriers for rs7221780, and T minor allele carriers for rs8066276) 58 were associated with worse 6-month GOS; neuroglobulin rs3783988 C allele carriers were associated with poor GOS at 3/6/12/24 months 63 ; ATP binding cassette C3435T C allele carriers were associated with worse 6-month GOS 61 ; AQP-4 rs3763043 T homozygotes were associated with worse GOS at 6 months 64 ; aromatase rs2470144 A allele carriers were associated with worse outcome at 6 months; 65 PARP-1 rs3219090 A allele/rs3219119 T allele carriers were associated with poor GOS at 6 months 70 ; and calcineurin PPP3CC rs2443504 AA carriers had increased risk of mortality at 12 months.…”
Section: Global Patient Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Although all of the tauopathies display these tau deposits, the tauopathies are differentiated by the tau isoforms and anatomic distribution. 32 Rare mutations in MAPT cause an autosomal dominant tauopathy (FTDP-17), which may manifest as several clinical phenotypes including frontotemporal dementia COMT, 54,55 ANKK1, 55,56 IL1A, 57 IL1B, 26,58 IL1RN, 59 DRD2, 55,56 TNF, 60 BDNF, [61][62][63] BCL2, 64 mtDNA haplotypes H, J, T, U, 65 mt-ND3, 66 p53, 67 ACE, 68 NGB, 69 ABCB1, 70,103 AQP4, 71 CYP19A1, 72 PARP1, 73 IL6, 74,75 VMAT2 76,77 Genes/loci implicated in poor chronic c outcomes after TBI b APOE4, [78][79][80][81] TMEM106B, 50 BDNF, [61][62][63] mt-ND3, 66 NGB, 69 PPP3CC 105 Genes/loci implicated in AD Early-onset AD: APP, 82 PSEN1, 82 PSEN2, 82 Late-onset AD: CR1, 83,84 INPP5D/SHIP1, 83,84 UNC5C, 85 HBEGF/PFDNI1, 86,87 MEF2C/TMEM161B, 83 TREM2, 88,89 CD2AP/ADGRF2, 83,84 HLA-DRB/HLA-DQB1,…”
Section: Microtubule-associated Protein Taumentioning
confidence: 99%
“…They found that ABCB1 rs1045642 (NC 000007.14:g.87509329A>G; AA) and ABCC1 rs4148382 (NC 000016.10:g.16144637G>A; GG) genotypes were associated with lower odds of unfavorable 6-month Glasgow Outcome Scale (GOS) scores, defined as GOS of 1-3 (odds ratio: 0.71 and 0.73, respectively) [15]. The finding with ABCB1 rs1045642 was reversed in a study by Wang et al who studied 182 patients with TBI [16]. They defined favorable outcomes as GOS of 3-5 and found that patients with the (AG, GG) genotypes were more likely to have favorable GOS scores at 6 months post TBI (odds ratio: 2.71) [16].…”
Section: Pharmacogenomics Of the Blood-brain Barriermentioning
confidence: 99%